The Expression of FOXE-1 and STIP-1 in Papillary Thyroid Carcinoma and Their Relationship with Patient Prognosis - Enas M. Fouad; Ola A Harb; Reham Amin Salem; Ola M El farargy; Fady M Habib; Loay M Gertallah (Iranian Society of Pathology, 2018)
Background and Objective: Most patients with papillary carcinoma of the thyroid gland (PTC) have favorable outcome, but since it has severe capability to invade the nearby tissues, there is a great risk of regional and distal lymph-nodes (LNs) metastases related to poor prognostic parameters, early recurrences, and distant metastasis that lead to bad patient outcome. Discovering other prognostic biomarkers for this cancer helps to detect early recurrences, invasion, expecting patient outcome, and possible use as therapeutic-targets for it. The fork-head-box-E-1 (FOX-E-1), with the alternative name of thyroid-transcription- factor-2 (TTF-2), is one of the transcription factors families that is huge and contains a special fork-head-domain. It has a significant role in the differentiation and maturation of thyroid-follicular cells. Stress-induced phosphor-protein-1 (STIP-1), with the alternative name of heat-shock-protein-(HSP)-organizing protein, is a 62.6-kD protein, with three parts of tetra-trico-peptide repeats (TPR), and is capable of interaction with heat-shock proteins forming structures that have plethora of roles in variable cellular processes; e.g., cell cycles regulations, transcriptions, and RNA splicing. The current study aimed at exploring the relationship between FOXE-1 and STIP-1 expressions, the clinicopathological parameters, prognosis, and survival of patients with PTC. Methods: The current study explored FOXE-1 and STIP-1 expressions by the immunohistochemical methods in 36 paraffin blocks retrieved from 36 patients of PTC, analyzed the relationships between their levels of expression, clinicopathological parameters, prognosis, and survival of patients. Results: The high expression levels for both FOXE-1 and STIP-1 in PTC were associated with larger size of the tumor, extra-thyroidal extension, vessels invasion, LNs spread (P <0.001), presence of distant metastases (P values = 0.005 and 0.012, respectively) and higher stages of the cancer (P values =0.012 and 0.042, respectively). The FOXE-1 over-expression was associated with shortened distant metastases free survival (DMFS) and shortened five-year overall survival rates (OS) (P <0.001). Conclusion: Patients with advanced PTC and unfavorable prognosis had high levels of both FOXE-1 and STIP-1 expressions.